Promoting small family businesses through OCOP program and tourism activities in rural areas in Vietnam: the case of Bac Giang Province - Le, Anh Thi Phuong; Kunasekaran, Puvaneswaran; Ravagan, Neethiahnanthan Ari; Le, Hung Ngoc; Nguyen, Tuan Thanh; Luong, Thang Vu (Emerald, 2022)
One Commune One Product (OCOP) program, a rural economic development program in Vietnam, aims to empower local communities for sustainable social and economic welfare development, protect the environment and preserve tradition. This study aims to employ this program associated with tourism to support small family businesses in rural areas cost-effectively. This study used the geographic location mapping method to design tourist routes that connect tourism resources with OCOP producers. A stakeholder approach was employed to identify suggested practical works that need to be implemented while developing this tourism initiative.Four rural districts of Bac Giang Province, a northern province in Vietnam known as the place of various indigenous people live and traditional craft villages. Many cultural and historical tourist sites have been chosen as sample areas for this study. By using Google map, based on the Bac Giang Tourist Map and a list of recognized OCOP products in Bac Giang Province, main tourist sites (16 locations) and small family businesses (known as cooperatives and households) that have OCOP products (17 places) in the four districts have been identified. Four notable tourist routes have been formed to propose four thematic tours (two 1-day tours and two 2 days-1 night homestay tours). Suggestions for related stakeholders to ensure the sustainability of this initiative are provided.This study is supposed to be a model of promoting small family businesses through OCOP programs and tourism activities in a sustainable way in Vietnam. The outcome of this study is in line with the stakeholder theory emphasizing the systematic connection of various stakeholders such as employees, suppliers, local communities, government agencies and others towards complex business sustainability. The results of the study cannot conclude the small family businesses in Vietnam because it adopts geographic location mapping alone. Moreover, this study focused on OCOP programs only. Future research can use other methods of primary data collection, especially from tourists' perspectives. Data triangulation can be done to explore and verify the tourist routes that have been formed according to the four thematic tours proposed. Future research could also compare hotels managed by family businesses with non-family businesses.This study is supposed to be a model of promoting small family businesses through OCOP programs and tourism activities in a sustainable way in Vietnam.